Restless Stillness - Jansone, Ivanda (My University, 2025)
The Master of Fine Arts thesis project consists of an artistic component, which was displayed as part of Kuvan Kevät exhibition from May 17th to June 15th, 2025, at the Academy of Fine Arts in Helsinki, and a written component titled Restless Stilness. The artistic component of the thesis comprises two charcoal drawings, Before and After, and eight photopolymer prints, Restless Stillness I-VIII.  One of the main subjects my thesis revolves around is time. I explore time both as subject and as structure. It appears as movement within narratives, as a temporal frame, but also as something to examine in itself—the ways we perceive it in life, in visual art, and in comics, along with the similarities and differences between those perceptions. Another central subject of this thesis is the portrayal of women smoking in art. The portraits of a woman smoking become a guiding thread through this framework, the main narrative. I consider how the smoking woman is not just a portrait, but also a reflection on gender inequality. In my work, however, the act of smoking becomes a gesture of reclaiming space and expressing resistance. I also play with context and content—how one shapes the other. When images are placed in sequence, side by side, their meanings begin to shift. The gaps between panels and portraits hold as much weight as the images themselves. The act of smoking, in a sense, takes place in these spaces between. I examine the relationship between fine art and comics in the context of medium and form, exploring questions of time in narratology, juxtaposed images, and non-linear storytelling. As an artist working across fine art, comics, printmaking, and publishing, I explore the definitions, similarities, and differences between these traditions through the lens of my own work. Rather than setting strict boundaries, I reflect on how I approach narrative in art through the language of comics.
Keywords: time; womanhood; woman's status; comic art; portraits (works of art); opinnäytteet; maisterit; fi=taidegrafiikka|sv=konstgrafik|en=Printmaking|